Status of Cadaver for Anatomy Education in Medical Schools of Nepal - Mishal, Jyoti; Mishal, Sonu; Shakya, Shuvechha; Gurung, Sanyukta (Nepal Journal of Health Sciences, 2024)
Introduction: Anatomy is a core subject in medical sciences where cadavers play a pivotal role in understanding the subject. As the number of medical institutions tends to grow the demand for medical resources is increasing. However, the sources of cadavers vary in different geographical regions due to differences in related laws and sociocultural aspects. The predominant sources of cadavers are donated, unclaimed and bequeathed bodies. Objective: This study aims to explore the status of cadavers in medical colleges of Nepal. Methods: A descriptive, cross-sectional study was conducted from 2023 to 2025 in 18 fully functioning medical colleges. Data was collected by a non-probability convenience sampling method. Professionals working in the anatomy departments were contacted via tele-communication after ethical clearance. The authors filled self-structured proforma sheets which included the number, sources, gender of cadavers and the total number students in the medical institutions. Results: Among all medical colleges there were 91 cadavers, predominantly of male gender in the academic year 2023/2024. A total of 1715 students were recruited in these medical colleges. The ratio of cadaver and students was 1:19 and the sources were mostly unclaimed. The ratio of cadaver and students ranged from 1:5 to 1:100. Conclusion: The cadavers being used in the medical colleges were mostly males and unclaimed bodies.